Cultural Dynamics in Community Service: Understanding Social Interventions for Better Outcomes - Ratih, Ratih (Journal Ligundi of Community Service, 2025)
Background. Cultural dynamics in community service play a crucial role in the success of social interventions. Understanding how these interventions are influenced by local cultural contexts is essential for achieving better outcomes in community service programs. Purpose. This study aims to explore the relationship between cultural dynamics and the effectiveness of social interventions within the context of community service. Specifically, it assesses how cultural factors impact community acceptance and participation in intervention programs. Method. The study involved 350 respondents from various cultural backgrounds participating in community service programs. Data were collected through questionnaires and analyzed using appropriate statistical methods to identify patterns and relationships. Results. Findings indicate that cultural dynamics significantly affect participation levels and the success of social interventions. Programs that consider local values and norms tend to be more readily accepted by communities. Additionally, notable differences in responses to interventions were observed based on cultural background. Conclusion. This research provides valuable insights for community service practitioners and policymakers. By understanding the cultural dynamics that influence social interventions, stakeholders can design more effective and responsive programs to meet community needs.